Hepatoprotective and antioxidant effi cacy of aqueous stem bark extracts of Balanites aegyptiaca (Linn.) Del. against acetaminophen induced liver injury in rats - Luqman A. Olayaki, Constance C. Jide-Ojo, Opeolu O. Ojo, Olusola O. Ladeji (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Traditional use of various extracts of Balanites aegyptiaca in the management of many diseases has been previously reported. Though oxidative stress is known to contribute to the development of many of the disease conditions on which extracts of B. aegytiaca have been found efficacious, effects of these extracts on free radical-induced lipid peroxidation is not well understood. This study investigated the protective effects of stem bark extracts of B. aegyptiaca on acetaminophen-induced lipid peroxidation in rats. Phytochemical analysis of the plant extract used was conducted. Following a 10 day pre-treatment with extracts of B. aegyptiaca, serum levels of thiobarbituric reactive substances (TBARS), vitamin C, cholesterol/phospholipids, catalase (CAT) activity as well as markers enzymes of hepatotoxicity were measured in rats administered with acetaminophen (2 mg/kg body weight). Results obtained indicated preponderance of alkaloids, flavonoids, glycosides, phenols, saponins, and tannins. Pre-treatment with extracts of B. aegyptiaca protected against acetaminophen-induced elevation of TBARS and marker enzymes of hepatotoxicity as well as inhibited the depletion of serum levels of vitamin C, CAT activity and phospholipids in a dose-dependent manner. Serum levels of cholesterol were not affected by acetaminophen intoxication or treatment with the plant extract. These results indicated that therapeutic actions previously linked with extracts of B. aegyptiaca might be a consequence of its antioxidative and hepatoprotective effects.